Industry revolution 4.0 and digital transformation - it’s implementation, opportunity and challenges in Bangladesh textile industry - Tushar, Ismail Hossain (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.